Untargeted metabolomics analysis reveals dynamic changes in co-fermentation with human milk-derived probiotics and Poria cocos - Wang, Qishan; Yang, Kai; Wei, Xinyue; Qiao, Weicang; Chen, Lijun (Frontiers in Microbiology, 2022)
Introduction To develop functional foods with traditional medicines and homologous food ingredients as well as human milk-derived probiotics, the co-fermentation process of two probiotics, Lactobacillus plantarum R9 and Lactobacillus gasseri B1-27, isolated from the human milk of healthy parturients and the traditional medicine and food homologous ingredient Poria cocos, were separately investigated. Results The Poria cocos fermentation broth at 2.5% significantly enhanced the total number of L. plantarum R9 (p = 0.001) and L. gasseri B1-27 (p = 0.013) after 20 h of fermentation, and Non-targeted metabolomics assays conducted before and after fermentation of the human milk-derived L. plantarum R9 and L. gasseri B1-27 using the 2.5% Poria cocos fermentation broth revealed 35 and 45 differential metabolites, respectively. A variety of active substances with physiological functions, such as L-proline, L-serine, beta-alanine, taurine, retinol, luteolin, and serotonin, were found to be significantly increased. Mannitol, a natural sweetener with a low glycemic index, was also identified. The most significantly altered metabolic pathways were pyrimidine metabolism, pentose phosphate, yeast meiosis, ABC transporter, insulin signaling, and mineral absorption, suggesting that co-fermentation of human milk-derived probiotics and Poria cocos may affect the metabolism of trace minerals, sugars, organic acids, and amino acids. Discussion Overall, we determined that the optimal concentration of Poria cocos to be used in co-fermentation was 2.5% and identified more than 35 differentially expressed metabolites in each probiotic bacteria after co-fermentation. Moreover, several beneficial metabolites were significantly elevated as a result of the co-fermentation process indicating the valuable role of Poria cocos as a functional food.